2021
DOI: 10.3390/ma14123295
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Thickness of Compact TiO2 Electron Transport Layer on the Performance of Planar CH3NH3PbI3 Perovskite Solar Cells

Abstract: In recent years, lead halide perovskites have attracted considerable attention from the scientific community due to their exceptional properties and fast-growing enhancement for solar energy harvesting efficiency. One of the fundamental aspects of the architecture of perovskite-based solar cells (PSCs) is the electron transport layer (ETL), which also acts as a barrier for holes. In this work, the influence of compact TiO2 ETL on the performance of planar heterojunction solar cells based on CH3NH3PbI3 perovski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Mesoporous TiO 2 thin films are widely utilized as electron transport layers in solar harvesting devices, such as dye-sensitized solar cells [1,2], perovskite solar cells [3,4], and photoelectrochemical cells [5]. However, the efficiency of electron transport in these TiO 2 thin films is hindered because of charge trapping, recombination, and grain boundary scattering effects [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous TiO 2 thin films are widely utilized as electron transport layers in solar harvesting devices, such as dye-sensitized solar cells [1,2], perovskite solar cells [3,4], and photoelectrochemical cells [5]. However, the efficiency of electron transport in these TiO 2 thin films is hindered because of charge trapping, recombination, and grain boundary scattering effects [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An ETL transports photoinduced electrons away from the perovskite, and at the same time, it serves as a blocking layer preventing direct contact between the holes and fluorine-doped tin oxide (FTO) [24,25]. Therefore, TiO 2 layers should be uniform, pinhole-free, and should completely cover the surface of FTO [26]. The optimal thickness of crystalline TiO 2 depends on the deposition technique and post-treatment of the layers.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal thickness of crystalline TiO 2 depends on the deposition technique and post-treatment of the layers. In the case of planar PSCs, the thickness of an ETL is in the range of 20-30 nm [26][27][28]. The deposition of a mesoporous (mp-TiO 2 ) layer on crystalline titanium dioxide provides a reduced carrier transport length and increased interfacial contact area, thereby facilitating efficient charge carrier collection and yielding the highest reported PCE values [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that the PCE of PSCs is generally dependent on thickness of the perovskite absorber [12][13][14][15]. Thickness of electron transport layers are also crucial for better efficiencies [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%